Site visits to initiate recruitment in a clinical trial: does it matter who conducts the visit? Protocol for implementation in trials. Issue 4 (November 2016) - Nollett, Claire; Kelson, Mark; Hood, Kerenza
Abstract: The Study Within a Trial (SWAT) program exists to 'embed research within research, so as to resolve uncertainties about the different ways of designing, conducting, analyzing, and interpreting evaluations of health and social care' (1). Published in this journal in 2013, a template for the first SWAT protocol outlined an investigation into the effects of site visits by the principal investigator on recruitment in multicentre randomized controlled trials (1). We have now designed a SWAT protocol to extend this question and ask 'does it matter who conducts the site visit?' Our aim is to provide a protocol that trials can implement to address this research question.